(untitled) (La U Investiga, 2017)
Prebiotics are non-digestible food substances that stimulate the growth or colon bacteria activity, and therefore prevent the appearance of functional complications, which can be avoided with the consumption of these food ingredients. For this reason, the study aims at developing a nutritional bar based on foods containing prebiotics, substances that benefit the health of the body; likewise, this food bar provides other important nutrients for the individual’s diet. The bar is prepared by hand, using supplies, utensils and equipment that can be found in a regular home and are available to all people. The following foods were mixed: oats, strawberries (coextruded), ground cinnamon, panela, raisins, grated dried coconut, honey, soybean oil, sesame, and vanilla and coconut essences. The chemical analysis used the ENSANUT food composition table, and it showed the following nutritional composition: 302.9 Kcal, 6.5 g of protein, 8.63 g of fats, 54.32 g of carbohydrates, 5, 4 g of fiber. Its cost was estimated at 0.90 . The time required to obtain the final product was approximately one hour, packaging included. There are several advantages when consuming this nutritive bar, besides stimulating the growth of beneficial bacteria in the colon, it provides an important nutrient input to help growth and development in children. It provides the necessary calories contribution, and macro and micronutrients, both necessary in daily diet.